Louis Mallet in the Crosshairs of The Times: Criticism of Actions of the British Diplomacy in Constantinople at the Beginning of the First World War - Hrachov, A. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2022)
The article is devoted to the publication of “A Mortifying Disclosure” in the British newspaper “The Times” on August 24, 1917, with criticism of British foreign policy towards the Ottoman Empire, in particular the actions of Louis Mallet, the British ambassador in Constantinople. The mentioned publication, as well as the discussion caused by it, are little covered in historiography. Much more information is provided by the primary sources, represented by the documents of the British National Archives (The National Archives, TNA), and also by the memoirs of the participants of researched events. In the mentioned article, Louis Mallet was criticized for short-sightedness and excessive credulity. According to the author of the publication, the Turkish grand vizier deceived the British ambassador, even when the choice of the Ottoman Empire in favor of entering the war on the side of the Central Powers became obvious. In turn, the fact that British diplomats failed to find out about the existence of the German-Turkish treaty became the basis for sharp criticism of the Foreign Office at all. In response to this publication, Louis Mallet spoke in defense of his actions in Constantinople. He was supported by other Foreign Office officials, including former Foreign Secretary Edward Grey. They argued that the Foreign Office was fully aware of the pro-German course of the Porte, but intended to delay the state of war with her as far as possible in order to prepare for the defense of Egypt, the Suez Canal and India. These circumstances led to the accommodating position of British diplomacy. The characteristics of both Mallet himself and the grand vizier of the Ottoman Empire, Said Helim, are separately analyzed from the point of view of historiography and their contemporaries. Also the importance of the defense of India and Egypt, its importance as a key factor in shaping the course of British diplomacy was researched. Finally, the work contains the author’s interpretations and evaluations of the analyzed events.